Interpersonal Musical Synchronization and Prosocial Behavior in Children: No Effects in a Controlled Field Experiment - Baier, Janina; Wöllner, Clemens; Wolf, Anna (Frontiers in Psychology, 2021)
Prosocial effects of music have recently attracted increased attention in research and media. An often-cited experiment, carried out under laboratory conditions, found that children at the age of four years were more willing to help each other after they had engaged in synchronous musical activities (Kirschner & Tomasello, 2010). The aim of the current study was to replicate this research under controlled field conditions in the children’s social environment, and to disentangle the musical synchronization effect by introducing a verbal interaction (singing together) and a motor interaction (tapping together) task, contrasted by an asynchronous control condition. In a between-participants design, no effects of musical synchronization nor the children’s gender were found. Furthermore, age was not related to prosocial behavior. Explanations are systematically discussed, yet it remains possible that the original effect found in 2010 might be overestimated and less consistently reproducible as previously assumed.